Four new genera of the Ceratonotus group (Copepoda, Harpacticoida), including the description of two new species - GEORGE, Kai Horst (European Journal of Taxonomy, 2021)
In the framework of an ongoing extensive phylogenetic evaluation of the Ceratonotus group (Copepoda, Harpacticoida, Cletodidae), Poropsyllus menzelae gen. et sp. nov. from the sublittoral of south-western Cyprus (eastern Mediterranean Sea) and Paratouphapleura aaroni gen. et sp. nov. from the western Weddell Sea (Antarctica) are described. Both new species fit the autapomorphies of the Ceratonotus group but cannot be assigned to any of the genera so far known. Instead, each new species presents a set of derived characters that justify their placement in new genera, Poropsyllus gen. nov. and Paratouphapleura gen. nov., respectively. Furthermore, a comparison of the species placed in Ceratonotus Sars revealed that because of exclusive morphological deviations, Ceratonotus concavus Conroy-Dalton, C. steiningeri George, C. tauroides George, and C. vareschii George should be excluded from Ceratonotus and transferred to a new monophylum, Tauroceratus gen. nov. Likewise, Polyascophorus monoceratus George, Wandeness & Santos is characterized by several apomorphies that justify its transfer from Polyascophorus to a new taxon, Pseudopolyascophorus gen. nov. The Ceratonotus group is therefore increased to 31 species assigned to 13 genera. The systematic modifications conducted and resulting phylogenetic consequences are discussed in detail.